Stability considerations associated with solvents, solutions and additives in quantitative chromatographic methods - MacNeill, Robert (Bioanalysis, 2019)
Towards the stabilization of the relevant antibodies, receptors, targets, synthetic peptides and oligonucleotides, as appropriate, the array of different reagents is just part of the foundation for reliable ligand-binding assay performance (1) and enough subject matter to make inclusion in this article unfeasible. Care must be taken, therefore, to assign the appropriate lifetimes to mobile phase components, washes and any isolated solvent or combination of solvents used in sample preparation or analysis. Buffer solutions, although wonderfully useful in quantitative LC-MS, are very often excellent growth media for microbes (2), as a consequence of the inherent dilute salt content. For protic organic solvents in the presence of carboxylic acids, ester formation may occur (3), and in the presence of esters, hydrolysis to the free acid can occur, especially when catalyzed by acidic or basic conditions.